Development of a Contextually-Based Animated Video on Acid–Base Solutions Using Powtoon Web Application - Mutiarasani, Dwi Rizki; Kamaludin, Agus (JTK (Jurnal Tadris Kimiya), 2025)
Engaging and pedagogically relevant learning media are essential for improving students’ conceptual understanding in chemistry, particularly on abstract topics such as acid–base solutions. This study aimed to develop a contextual animated video using the Powtoon web application to enhance student engagement and comprehension through real-life connections. The development followed the 4D model (Define, Design, Develop, Disseminate) and was conducted at a public senior high school in Yogyakarta. Participants included chemistry education lecturers (as media and content experts), high school chemistry teachers (for practicality evaluation), and 11th-grade science students (for readability testing). The animation incorporated core elements of contextual learning, such as inquiry, questioning, learning community, modelling, and reflection, to foster deeper understanding. Validation results indicated excellent quality, with ideal scores of 95% from media experts and 90% from content experts. Teachers rated the practicality at 92%, while students rated the video’s readability at 95%. All evaluations were categorized as “very good.” Quantitative data were analyzed descriptively using ideal percentage scores. These findings demonstrate that the developed animation is both pedagogically sound and technically effective in supporting student learning. This research contributes to the field of chemistry education by offering an accessible digital resource that supports contextualized instruction and increases student motivation and understanding of acid–base concepts.